A Voice Sweeter than Salt: Toyin Falola and the Construction of Subaltern Narrative Space - Ben Weiss (Yoruba Studies Review, 2021)
Gayatrl Spivak is arguably most recognized for her 1988 intervention in the dialogue of Subaltern Studies. It is within the intellectual rift of Spiva k's "Can the Subaltern Speak?" that I explore the narrative of Toyin Falola's memoir, A Mouth Sweeter than Salt. While Spivak concludes that the subaltern cannot speak because of the subaltern's placement within existing knowledge production, Falola's "Mouth" articulates a formation that says otherwise. Indeed, in A Mouth Sweeter than Salt, Falola's status In the subalternlty of a decolonlzlng Nigeria depicts a powerful subaltern voice with deep implications for knowledge, representation, authorial location, multifaceted identity paradox, and most of all, the tendrils of modernity.